Osijek: Mapping the Fictional and the Physical City: The Spatiotemporal and Cultural Identity of Osijek, Croatia - Novak, Sonja; Sioli, Angeliki (Writingplace, 2023)
Because of its status as the fourth largest city in Croatia, Osijek is considered an intermediate European city. It is the administrative, economic and cultural centre of eastern Croatia, located on the River Drava, and has a rich, multicultural history that is reflected in its tangible and intangible urban identity. It is famous for its historical Fort Tvrđa and its European Avenue, the most representative street of Austro- Hungarian Secession architecture, but also for its specific sociolects that have been a part of its everyday life. Within the COST Action Writing Urban Places: New Narratives of the European City, Osijek was host to the doctoral training school ‘Urban Chronicles in Empirical Context’ (April 2022) and a short-term scientific mission to investigate the ‘other’ perspectives of the city (August 2022). As events that fostered the training, research, and the networking of international and national young researchers, doctoral candidates and members of academia, they helped to raise awareness of the notion of urban identity of a city as a complex of its physical (geography, architecture, infrastructure) and ephemeral manifestations (literature, culture, history) through time. As such, the events functioned as an outreach, linking the involved participants to their own responsibilities to the city as potential and future policymakers. The following chapter focuses on elements of the city of Osijek as presented through the literary point of view of local authors from the mid-twentieth to the early twenty-first century.